Penggunaan E-Bekal Dalam Transaksi Digitalisasi UMKM Pesantren Nurul Jadid - Junaedi, Deddy; Firdausi, Jinani; Khaira, Muftihatul; Ifadah, Zainuna; Mardhatillah, Debby; Lutfiana, Evi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
E-Bekal is a digital payment innovation designed to support transaction activities of micro, small, and medium enterprises (UMKM) within Nurul Jadid Islamic Boarding School. This study aims to explore how e-Bekal is implemented and utilized as a cashless payment tool by students (santri) and business operators. The research adopts a descriptive qualitative method using a case study approach. Data were collected through in-depth interviews with UMKM actors and e-Bekal users, participatory observations, and documentation of digital transaction activities. The findings reveal that e-Bekal significantly facilitates transaction processes. It enhances operational efficiency by automating the recording of payments and encourages the growth of digital transaction culture within the pesantren. However, the implementation still faces several challenges. These include low digital literacy among users, the persistence of manual transaction recording by business owners, occasional transfer errors, and a lack of proper socialization and training. These factors hinder the optimal use and expansion of the e-Bekal system despite its clear benefits.